2015
DOI: 10.1055/s-0035-1549942
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Osteomyelitis einer Endphalanx am Finger durch Raoultella ornithinolytica

Abstract: We report on a case of osteomyelitis of a distal phalanx of the right ring finger of a 62-year-old patient, which occurred 11 months after transosseous-transungual refixation of a closed flexor digitorum profundus tendon avulsion caused by Raoultella ornithinolytica. R. ornithinolytica is an encapsulated Gram-negative aerobic bacillus. In the literature only 13 cases of human infection by R. ornithinolytica are mentioned. To the best of our knowledge, this is the first case of an osteomyelitis caused by R. orn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In a retrospective study from four university hospital centres and 187 R. ornithinolytica isolates this was associated with diseases such as osteomyelitis, meningitis, cerebral abscess, mediastinitis, pericarditis, conjunctivitis, and otitis [14,15]. Also, a case report has been reported after pancreaticoduodenectomy [16] as well as in diabetic limbs [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study from four university hospital centres and 187 R. ornithinolytica isolates this was associated with diseases such as osteomyelitis, meningitis, cerebral abscess, mediastinitis, pericarditis, conjunctivitis, and otitis [14,15]. Also, a case report has been reported after pancreaticoduodenectomy [16] as well as in diabetic limbs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Following a literature review, only one case of Raoultella osteomyelitis has been reported [ 4 ]. This involved a distal phalanx infected with R. ornithinolytica 11 months after surgical fixation of a tendon avulsion [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following a literature review, only one case of Raoultella osteomyelitis has been reported [ 4 ]. This involved a distal phalanx infected with R. ornithinolytica 11 months after surgical fixation of a tendon avulsion [ 4 ]. A case of temporomandibular joint infection caused by R. ornithinolytica was recently reported in a 38-year-old patient 5 weeks after temporomandibular joint arthroscopy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only five cases of chronic osteomyelitis have been reported to date, including one case of osteomyelitis of a distal phalanx of the right ring finger [4] , one case of tibia pandiaphyseal osteomyelitis (an osteomyelitis extending to the entire the diaphysis or as involvement of the opposite metaphysis), two cases of chronic osteomyelitis of diabetic foot infections and one case of foot osteomyelitis related to a peripheral artery disease [2] .…”
Section: Discussionmentioning
confidence: 99%
“…The main treatment of the cases of osteoarticular infection caused by R. ornithinolytica reported in the literature has been surgical lavage and debridement followed by prolonged antimicrobial treatment. The duration of treatment varied from 30 to 90 days [2] , [4] . All of these cases recovered, but one case of tibia pandiaphysitis and one case of chronic osteomyelitis in diabetic foot infection required amputation [2] .…”
Section: Discussionmentioning
confidence: 99%